Antidiabetic effects of Brugmansia aurea leaf extract by modulating the glucose levels, insulin resistance, and oxidative stress mechanism - Fatima, Nisar; Anwar, Fareeha; Saleem, Uzma; Khan, Aslam; Ahmad, Bashir; Shahzadi, Irum; Ahmad, Hammad; Ismail, Tariq (Frontiers in Nutrition, 2022)
Background Ethnopharmacological relevance: Brugmansia, a genus of the Solanaceae family, has historically been utilized in many different parts of the world as an anti-inflammatory for treating skin infections, wounds, and bodily aches and pains. The current study aimed to investigate the potential benefits of a methanolic extract of Brugmansia aurea in the management of diabetes and underlying complications in alloxanized-induced diabetic rats. Materials and methods Animals were divided into nine groups (n = 6). Four groups received different standard oral hypoglycemic agents; three groups received 100, 200, and 400 mg/kg of B. aurea leaf extract for six consecutive weeks, and the remaining two were normal and disease control groups. All groups received alloxan (150 mg/kg) except for the normal control. Only those animals whose glucose levels were raised to 200 mg/dl were selected for the study. After a 6-week dosage period, various biochemical parameters, as well as HbA1c, antioxidant profile, oral glucose tolerance test (OGTT), insulin sensitivity, histopathology, and insulin resistance, were measured and compared with the untreated diabetic group. Results Brugmansia aurea leaf extract at a dose of 400 mg/kg showed potent antidiabetic activity by reducing blood glucose levels (p < 0.001) after 6 weeks of treatment. OGTT data showed that B. aurea exhibited significant (p < 0.001) glucose tolerance by significantly reducing blood glucose levels in just 2 h post-treatment. Other tests showed that plant extract significantly increased (p < 0.001) insulin sensitivity and decreased (p < 0.001) insulin resistance. The biochemical profile showed reduced triglyceride and cholesterol, while the antioxidant profile showed restoration of antioxidant enzymes in the pancreas, kidney, and liver tissues of treated rats. Conclusion The present study indicated that crude extracts of B. aurea increase insulin sensitivity and reduce hyperlipidemia in diabetic rats, which rationalizes the traditional medicinal use of this plant as an antidiabetic agent.